PELATIHAN PENGEMBANGAN SISTEM MANAJEMEN DATA MAHASISWA BERBASIS AI MENGGUNAKAN GOOGLE APPS SCRIPT BAGI MAHASISWA - Nurfauziah; Dian Atmasani; Nur Athiyyah Fadhillah; A. Muzawwirah Patawaria; Indra Sukma (Journal of Engineering Service and Innovation, 2026)
The development of digital technology and artificial intelligence (AI) has prompted higher education institutions to enhance their students' competencies in the development of applications and the management of information systems based on intelligent technology. However, some students of the Electronics Engineering and Information Technology Department still find it difficult to understand the practical implementation of programming and web application development. Therefore, the purpose of this community service activity is to enhance students' ability to develop web applications for managing student data based on AI. The activity is carried out through a practical training method and project-based learning, consisting of a preparation stage, implementation stage, and mentoring stage. The training programme covers web application development, database management, implementation of student data management system features, and the use of AI in application development. The results of the activity show that participants were able to understand the basic concepts of web application development and successfully developed an AI-based student data management system application with login, student data management, search, edit, delete and report features. In addition to improving technical skills, the training programme also increased the students' motivation to learn, their logical thinking abilities, their creativity, and their problem-solving skills. Therefore, this training activity can be an effective way to support the improvement of the quality of human resources in the field of higher vocational education and training, so that they are better prepared to face the challenges of digital technology and AI-based industry.